Incorporating architectural modelling with state-based reliability evaluation. (2017) - Chen, Luxi; Huang, Linpeng; Li, Chen; Wu, Xiwen
In the system development, it is quite important to evaluate non-functional property qualities on the architecture for making early adjustment decisions. However, in current practice, functional architectural modelling and non-functional quality evaluation are often implemented separately. And most architecture description languages fail to specify architecture evolution to implement adjustment. It is essential to propose a mechanism implementing architecture level evaluation, and supporting architecture evolution. With these considerations, we present an architecture reliability evaluation and evolution framework, which is based on the architecture description language - Breeze/ADL. First, by using Breeze/ADL, the system architecture is specified with reliability properties. Second, Breeze/ADL specifications are turned into a state view Markov chain (MC) model. This model helps to evaluate the reliability and conduct importance analysis to identify the critical module. Third, based on the evaluation result, the evolution mechanism by Breeze/ADL will raise an adjustment solution to improve the reliability.